2013
DOI: 10.1186/2051-5960-1-55
|View full text |Cite
|
Sign up to set email alerts
|

The systemic iron-regulatory proteins hepcidin and ferroportin are reduced in the brain in Alzheimer’s disease

Abstract: BackgroundThe pathological features of the common neurodegenerative conditions, Alzheimer’s disease (AD), Parkinson’s disease and multiple sclerosis are all known to be associated with iron dysregulation in regions of the brain where the specific pathology is most highly expressed. Iron accumulates in cortical plaques and neurofibrillary tangles in AD where it participates in redox cycling and causes oxidative damage to neurons. To understand these abnormalities in the distribution of iron the expression of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
172
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(187 citation statements)
references
References 101 publications
(110 reference statements)
10
172
1
4
Order By: Relevance
“…We speculate that oxidative stress induced decrease in native APP as the cause for Fpn degradation. Our study also support the recent findings of reduced Fpn level in brain in Alzheimer's disease [40] in which native APP level is reduced with simultaneous generation of increased oxidative stress due to Abeta formation [5].…”
Section: Discussionsupporting
confidence: 92%
“…We speculate that oxidative stress induced decrease in native APP as the cause for Fpn degradation. Our study also support the recent findings of reduced Fpn level in brain in Alzheimer's disease [40] in which native APP level is reduced with simultaneous generation of increased oxidative stress due to Abeta formation [5].…”
Section: Discussionsupporting
confidence: 92%
“…This hypothesis is further supported by the previous findings of significant reduction of Fpn levels in hippocampal lysates from AD brains, which corroborate the impairment of Fe export also in the brain [58].…”
Section: Discussionsupporting
confidence: 81%
“…In both diseases, iron accumulation has been implicated in the pathology and pathogenesis (Good, 1992;Martin, 2008;Ayton, 2015). Interestingly, dysregulation of Hepcidin has also been observed in Parkinson patients (Raha, 2013). VPS35 involvement in iron regulation inferred from this study is consistent with the reported disease relevance of VPS35 and iron elevation implicated in the pathogenesis of the two progressive neurodegenerative diseases.…”
Section: Discussionsupporting
confidence: 80%